10*3=30
30*3=90
90*3=270
270*3=810
or
10*3^1=30
10*3^2=90
10*3^3=270
10*3^4=810
the next two terms of this sequence are 270 and 810.
The equivalent expression of x^3 (x^2 + 5x + 7) is x^5 + 4x^4 + x^4 + 8x^3 - x^3
<h3>How to determine the equivalent expression?</h3>
The expression is given as:
x^3 (x^2 + 5x + 7)
Expand the expression
x^3 * x^2 + x^3 * 5x + x^3 * 7
Evaluate the product
x^5 + 5x^4 + 7x^3
Expand the expression
x^5 + 4x^4 + x^4 + 8x^3 - x^3
Hence, the equivalent expression of x^3 (x^2 + 5x + 7) is x^5 + 4x^4 + x^4 + 8x^3 - x^3
Read more about equivalent expression at:
brainly.com/question/27911936
#SPJ1
We know that
cos²(theta)=0.21
sin²(theta)+cos²<span>(theta)=1
</span>sin²(theta)=1-cos²(theta)------> sin²(theta)=1-(0.21)-----> 0.79
sin(theta)=√0.79
sin(theta)=0.89
the answer is
the value of sin(theta) is 0.89
$58+ $12.76= $70.76 total
Final answer: $70.76